Acceptance of customer on using online food delivery applications - Alicia Chye Shen Li; Gelory Greanchey Majikol; Nur Ziana Muhammad Zamri; Izni Zulaikha Kamarezaman (2021)
Nowadays, there has been a rise of online food delivery applications as it is now widely used, especially in this time of COVID-19 pandemic. Food businesses and restaurants alike are expected to provide food delivering services now in hopes to keep the business alive. Research has shown that there are a few important factors that influence the public in using online food delivery applications. This study aims to determine three main factors that play a role in the acceptance of using online food delivery applications. These three factors are performance expectation, social influence and perceived trust. For the purpose of gathering information and data, an online questionnaire has been distributed through social media. The results of the study shows that performance expectation, social influence and perceived trust have a significant relationship to customers’ acceptance of using online food delivery applications. Based on Pearson Correlation Coefficient analysis, it is said that there are positive correlations between all these factors and the acceptance of customers on using online food delivery applications. The most influential factor of customer acceptance is performance expectation with the highest average mean of 4.07. In Malaysia, it can be said that majority of online food delivery application users prioritised both performance expectation and perceived trust more compared to social influence.